2003
DOI: 10.1111/1540-4781.00195
|View full text |Cite
|
Sign up to set email alerts
|

The Stability of General Foreign Language Classroom Anxiety across English and French

Abstract: The present study examined the stability of the general foreign language classroom anxiety construct across English and French. Preservice teachers from two western universities in Venezuela, who were majoring simultaneously in these two foreign languages, participated in the study. The students represented a variety of levels within each language. They completed two Spanish versions (one for each language) of the Foreign Language Classroom Anxiety Scale (FLCAS; Horwitz, Horwitz, & Cope, 1986). Separate analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
95
2
5

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(112 citation statements)
references
References 26 publications
8
95
2
5
Order By: Relevance
“…L2 learners' perceived worry and emotionality related to foreign language learning could still be empirically separated from a general test anxiety variable (Horwitz, 2001). They only moderately correlated across different foreign languages and were associated with significantly lowered language outcomes (Clément, Dörnyei & Noels, 1994, Ehrman, 1996Gardner, 2007;MacIntyre & Gardner, 1994;Rodriguez & Abreu, 2003;Sparfeldt, Schilling, Rost, Stelzl & Peipert, 2005). As predicted from a cognitive-motivational perspective, their relationships to subjective competence beliefs and general self-esteem characteristics appeared closer than to the actual performance scores (Bailey, Onwuegbuzie & Daley, 2000;Ehrman, 1996;Gardner, Masgoret & Tremblay, 1999;Kitano, 2001;MacIntyre, Noels & Clément, 1997;MacIntyre, Baker, Clément & Donovan, 2002;MacIntyre & Gardner, 1994;Mills, Pajares & Herron, 2007;Onwuegbuzie, Bailey & Daley, 1999, 2000b.…”
Section: Research On L2 Learners' Anxietymentioning
confidence: 93%
“…L2 learners' perceived worry and emotionality related to foreign language learning could still be empirically separated from a general test anxiety variable (Horwitz, 2001). They only moderately correlated across different foreign languages and were associated with significantly lowered language outcomes (Clément, Dörnyei & Noels, 1994, Ehrman, 1996Gardner, 2007;MacIntyre & Gardner, 1994;Rodriguez & Abreu, 2003;Sparfeldt, Schilling, Rost, Stelzl & Peipert, 2005). As predicted from a cognitive-motivational perspective, their relationships to subjective competence beliefs and general self-esteem characteristics appeared closer than to the actual performance scores (Bailey, Onwuegbuzie & Daley, 2000;Ehrman, 1996;Gardner, Masgoret & Tremblay, 1999;Kitano, 2001;MacIntyre, Noels & Clément, 1997;MacIntyre, Baker, Clément & Donovan, 2002;MacIntyre & Gardner, 1994;Mills, Pajares & Herron, 2007;Onwuegbuzie, Bailey & Daley, 1999, 2000b.…”
Section: Research On L2 Learners' Anxietymentioning
confidence: 93%
“…Extraverts, high-P and low-N participants reported lower levels of FLA in English. Rodriguez and Abreu (2003) examined the stability of the general foreign language classroom anxiety construct across foreign languages. Their participants were university students who were majoring simultaneously in English and French.…”
mentioning
confidence: 99%
“…Motivation encourages learners in their FL learning whereas anxiety interferes with it. Rodríguez and Abreu (2003) argue that these effects of motivation and anxiety might explain, at least partially, the relatively low levels of general FL anxiety in their study. Similar anxiety levels are found in the study by Pérez-Paredes and Martínez-Sánchez (2000 with Spanish students learning English.…”
Section: Introductionmentioning
confidence: 88%
“…The levels of foreign language anxiety experienced by learners may be determined by whether English is studied voluntarily or as a compulsory degree subject. A key study on this specific issue was undertaken in Venezuela by Rodríguez and Abreu (2003) with preservice English language teachers. The authors noted that participants' mean language anxiety score was lower than the scores reported in other studies (see below).…”
Section: Introductionmentioning
confidence: 99%